Insular destinies - Kitromilides, Paschalis, author.
1 online resource
Keywords: In this collection, an eminent authority on the history of political thought and on the intellectual history of modern Hellenism employs his twin academic specializations in political science and in intellectual history to understand the intricacies of the historical experience of his native island. Writing in a perspective inspired by the work of Fernand Braudel, he attempts in a series of studies in cultural and social history to recover lost and overlooked aspects of the collective destinies of Cyprus and the Cypriot diaspora in the centuries of Ottoman rule, a period of critical significance for the survival of the people of the island. He then turns to a penetrating analysis of the politics of the Cyprus Question. The pertinent studies collected in this volume bear the imprint of the deep soul-searching by the younger generation of Cypriot scholars at the time of the tragedy of 1974 over what went so wrong that their country was exposed to foreign invasion, occupation and division. The hints at answers to these questions offered by the author's interdisciplinary and critical treatment of the subject make this work an indispensable aid to anyone wishing to grasp the deeper antinomies and dilemmas immanent in the Cyprus Question.